DEVELOPMENT OF GUIDED INQUIRY LEARNING MODULES ON BIOTECHNOLOGY MATERIALS - Wahyuni Rahayu; Tiurlina Siregar (Jurnal Ilmu Pendidikan Indonesia, 2023)
This study aims to feasibility of science modules on guided inquiry-based biotechnology materials and improve learning outcomes using modules. The sample in this study were students in class IX F at SMP Negeri 2 Manokwari with a total of 36 students. Research results show that: 1). The feasibility of the module from the material expert validator was 86% in the very good category, the teacher's response was 82% in the very good category, and the results of small-scale trials were 87% in the very good category. 2) The average percentage of student learning activeness is 84% with a very active category in guided inquiry-based biotechnology material. 3) Increasing learning outcomes with an average n-Gain test of 0.49 in the medium category